Model for Predicting Hope According to the Attachment Styles and Time Perspective with the Mediation Role of Psychological Resilience in the University Students - Zohre Zohoori Zangeneh; sozan emami pour; Anita Baghdasarians (پژوهش‌های کاربردی روانشناختی)
The objective of the current study was to develop a model for predicting hope in university students that takes into account the time perspective and attachment patterns, with psychological resilience serving as a mediator. The research method was descriptive-correlational and pathway analysis. The study’s statistical population comprised all undergraduate students at non-state universities in Tehran during the academic year 2019-2020. 480 students (312 females and 168 males) were selected through the clustered random sampling method to comprise the statistical sample. Adult Attachment Styles (AAS), Zimbardo Time Perspective Inventory (ZTPI), Connor-Davidson Resilience Scale (CD-RISC), and Adult Domain-Specific Hope Scale (DSHS) comprised the questionnaires that were implemented. The data analysis was conducted through pathway analysis via SPSS and AMOS version 23. The findings indicated that students' hope is significantly correlated with their psychological resilience, time perspective, and secure, avoidant, and ambivalent attachment styles (p<0.01). Moreover, secure, avoidant and ambivalent attachment styles, time perspective and psychological resilience have significant direct effect on the students’ hope (p<0.01). Furthermore, the results of the Bootstrap analysis indicated that psychological resilience plays a substantial mediating role in the relationship between attachment styles and time perspective (p<0.01). The model finally achieved a satisfactory fit. Taking the significant mediation role of psychological resilience, it is necessary for the therapists and consultants to increase the students’ hope through training psychological resilience.